Hubungan Intensitas Mendengarkan Musik Populer Terhadap Kecerdasan Emosional Remaja Akhir di Universitas Bali Internasional - Ni Putu, Septian Eka Cahya Dewi; Novianti Astaningtias, Ni Made Irene; Suari Dewi, Anak Agung Sagung (Bali International Scientific Forum, 2023)
Abstract Adolescence is known as a period of storm and stress, where there is emotional upheaval accompanied by physical growth. Changes in the development of late adolescence affect the emotional condition of late adolescence. Several studies explain that music helps increase emotional intelligence. Individuals tend to listen to music to change moods, one of which is when individuals feel anxious. One of the genres of music that is popular with adolescents is popular music. This study aims to determine the relationship between the intensity of listening to popular music and the emotional intelligence of late adolescents at the Bali International University.        This study uses simple linear regression statistical analysis. The participants in this study were active students of class 5 of the Bali International University with an age range of 18-21 years old. The sampling technique of this research used purposive sampling technique. The scale used in this study were the intensity scale of listening to popular music to measure the intensity of adolescents in listening to popular music, and the emotional intelligence scale to measure the emotional intelligence of adolescents. Data retrieval is carried out via google form.        The results of the study using simple linear regression obtained a significance value of 0.000 (α <0.05) with a regression coefficient of 0.951 which means that there is a positive relationship between the intensity of listening to popular music with the emotional intelligence of adolescents at the Bali International University. If the intensity of listening to popular music is high, the emotional intelligence of adolescents will be high, and vice versa. The intensity of listening to music contributes 75.3% to emotional intelligence and 24.7% are influenced by other factors.